2018
DOI: 10.1186/s12889-018-5180-8
|View full text |Cite
|
Sign up to set email alerts
|

High HIV risk and syndemic burden regardless of referral source among MSM screening for a PrEP demonstration project in Toronto, Canada

Abstract: BackgroundTo maximize public health impact and cost-effectiveness, HIV pre-exposure prophylaxis (PrEP) must reach individuals at high HIV risk. Referrals for PrEP can be self- or provider-initiated, but there are several challenges to both. We assessed whether HIV risk differed by referral source among gay, bisexual and other men who have sex (gbMSM) screening for an HIV PrEP demonstration project.MethodsPREPARATORY-5 was an open-label PrEP demonstration project enrolling gbMSM at high risk of HIV acquisition … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…A study using a national sample among 1033 HIV-negative GBMSM in the United States observed a prevalence of depression (as measured by the 20-item Centre for Epidemiological Studies Depression scale) at 26.7%, sexual compulsivity at 13.8%, and polydrug use at 8% [7] . From our study and others, the prevalence of depression among PrEP using GBMSM could be considered comparable to the general U.S. GBMSM population (11–40%), while prevalence of sexual compulsivity (31%), alcohol use disorder (28–40%), and drug use disorder (36–37%) were all higher [ 12 , 13 , 23 ]. Notwithstanding the differences in mental health assessments and demographic composition between studies, the relatively higher prevalence of these disorders emphasizes the importance of addressing mental health in GBMSM who initiate PrEP.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…A study using a national sample among 1033 HIV-negative GBMSM in the United States observed a prevalence of depression (as measured by the 20-item Centre for Epidemiological Studies Depression scale) at 26.7%, sexual compulsivity at 13.8%, and polydrug use at 8% [7] . From our study and others, the prevalence of depression among PrEP using GBMSM could be considered comparable to the general U.S. GBMSM population (11–40%), while prevalence of sexual compulsivity (31%), alcohol use disorder (28–40%), and drug use disorder (36–37%) were all higher [ 12 , 13 , 23 ]. Notwithstanding the differences in mental health assessments and demographic composition between studies, the relatively higher prevalence of these disorders emphasizes the importance of addressing mental health in GBMSM who initiate PrEP.…”
Section: Discussionmentioning
confidence: 74%
“…High levels of drug use among GBMSM PrEP users have been reported previously [ 10 , 12 , 13 ]. In our study, participants reported using most of their drugs 2–4 times a month or less.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have similarly found elevated rates of mood disorders among patients who use PEP and PrEP. 30 - 32 Although no significant correlation was identified between anxiety or depression and PrEP discontinuation, previous studies have identified this relationship. 33 As such, mood disorders may be the reason PrEP is needed (in that sexual practices that can transmit HIV could be the manifestation of depression or anxiety) and might be reason it is not used in an ongoing fashion (in that these illnesses undermine retention in care).…”
Section: Discussionmentioning
confidence: 94%
“…We recruited participants through self-referral and provider referral between Oct. 16 and Dec. 30, 2014, as previously described. 17 English-speaking men aged 18 years or more were eligible if they reported having sex with men, tested nonreactive on a fourth-generation HIV test (Architect antigen/antibody combo assay, Abbott Laboratories), had a creatinine clearance rate of 60 mL/min or greater by the Modified Diet in Renal Disease formula, reported condomless receptive anal sex over the preceding 6 months and scored 10 or higher on the HIV Incidence Risk Index for MSM, a recommended cut-off value for identifying candidates for preexposure prophylaxis. 18 Exclusion criteria included symptoms or signs of HIV seroconversion, use of pre-or postexposure prophylaxis within the preceding 3 months, concomitant therapy with nephrotoxic or immunomodulatory drugs, hepatitis B surface antigen positivity, high risk of osteoporosis, enrolment in another HIV prevention trial or perceived inability to adhere to the study protocol.…”
Section: Participantsmentioning
confidence: 99%